Influence of the structure of poly (L-lactic acid) electrospun fibers on the bioactivity of endothelial cells: proliferation and inflammatory cytokines expression. Issue 3 (11th February 2017) - Liu, Xiaoyan; Zhang, Xiazhi; Wu, Keke; Yang, Wufeng; Jiao, Yanpeng; Zhou, Changren
Abstract: Electrospinning has been used to fabricate random and aligned poly (L-lactic acid) (PLLA) fibers with three kinds of diameter under optimal conditions. The main purpose of this paper was to investigate the influence of the diameter and orientation of fibers on the bioactivity of endothelial cells, especially on the inflammatory cytokines expression. The morphology of electrospun fibers and the cells on the fibers after 3 and 6 days culture were observed by scanning electron microscopy. Also the cell proliferation activity and cell cycle were tested and the results showed that the random fibers were more favorable for endothelial cells growth. The effect of PLLA film (served as a control) and six kinds of PLLA fibers mats on the inflammatory cytokines expression after cells incubated for 2 and 4 days were investigated. It was concluded that there was more intense inflammatory cytokines expression by cells on flat PLLA film than that on electrospun fiber mats. Also the fiber diameter has greater effect on the activity and inflammatory cytokines expression of endothelial cells than the fiber orientation, in which fibers with smaller size has weaker inflammatory reaction.